"A Silent Battle": Using a Feminist Approach to Support Couples after Miscarriage. Issue 1 (2nd April 2020) - Hiefner, Angela R.
ABSTRACT: The lack of recognition and understanding of miscarriage as a significant loss often leaves bereaved parents with less social support to help them navigate their grief. In a phenomenological study of parents' experiences of miscarriage, a theme emerged regarding disenfranchisement and the norm of silence surrounding early pregnancy loss. This theme contributes to overwhelming evidence that miscarriage is a unique loss with additional challenges. This paper will discuss this theme of disenfranchisement and describe how a feminist approach to couples therapy can provide greater support to parents experiencing this loss.